Impact of thrombolysis in acute ischaemic stroke without occlusion: an observational comparative study. (24th May 2016) - Ajili, N.; Decroix, J. P.; Preda, C.; Labreuche, J.; Lopez, D.; Bejot, Y.; Michel, P.; Sévin‐Allouet, M.; Sibon, I.; Vergnet, S.; Wang, A.; Sanda, N.; et al.
Abstract : Background and purpose: The impact of intravenous recombinant tissue plasminogen activator (IV‐rtPA) in patients with acute ischaemic stroke (AIS) but no arterial occlusion is currently a matter of debate. This study aimed to assess functional outcome of such patients with respect to IV‐rtPA use. Methods: A retrospective case−control analysis was performed comparing the outcome of AIS patients without arterial occlusion with or without IV‐rtPA use. Patients were selected from prospective consecutive observational registries of five European university hospitals. The primary study outcome was excellent outcome at 3 months after stroke, as defined by a modified Rankin Scale (mRS) 0–1. Results: A total of 488 patients without arterial occlusion documented by angiography were included in the present study; 300 received IV‐rtPA and 188 did not. No between‐group difference was found for excellent outcome before and after adjustment for baseline characteristics (adjusted odds ratio for no IV‐rtPA use 0.79, 95% confidence interval 0.51–1.24, P = 0.31). Similar results were found for favourable outcome (defined as a 90‐day mRS of 0–2) whereas a higher rate of early neurological improvement was found in IV‐rtPA‐treated patients (adjusted odds ratio 1.99; 95% confidence interval 1.29–3.07, P = 0.002). Sensitivity analyses yielded similar results. Conclusions: Our study suggests that AIS patients without visible arterial occlusion treated with IV‐rtPA may have no better outcome at 3 months than those untreated. However, only a randomized controlled trial would provide a definitive answer about the impact of rtPA in acute stroke patients without occlusion. Until then, these patients should be treated by rtPA as recommended.